Evaluation of vehicles' active seat suspension system using wavelet analysis. (October 2020) - Błażejewski, Andrzej; Głowiński, Sebastian
In this work, the dedicated test stand was applied to investigate the human body–vehicle seat system. The particular signals were measured by accelerometers placed on the seat and the human head. The horizontal vibrations were applied as the input to the system. As an alternative to the classical Fourier approach, the wavelet transfer function was introduced to describe the effectiveness of particular seat suspension. The human head reaction was investigated as the system output.